2022
DOI: 10.3390/antiox11020296
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection against Aminochrome Neurotoxicity: Glutathione Transferase M2-2 and DT-Diaphorase

Abstract: Glutathione is an important antioxidant that plays a crucial role in the cellular protection against oxidative stress and detoxification of electrophilic mutagens, and carcinogens. Glutathione transferases are enzymes catalyzing glutathione-dependent reactions that lead to inactivation and conjugation of toxic compounds, processes followed by subsequent excretion of the detoxified products. Degeneration and loss of neuromelanin-containing dopaminergic neurons in the nigrostriatal neurons generally involves oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 96 publications
1
17
0
Order By: Relevance
“… 57 In this context, it is important to recall that DAT is also expressed in astrocytes and macrophages, which contribute to DA clearance from the synaptic cleft. 48 , 49 The increased number of CD68- and GFAP-positive cells in AAV-TYR-injected animals could thus favor an increased DA uptake and metabolism in glial cells, which is consistent with increased 3MT levels observed in the ventral midbrain of AAV-TYR-injected animals at 2 months post-AAV injection ( Supplementary Table 6 ) and that could restrict the amount of DA available to be re-uptaken by neuronal DAT. All these changes in DA metabolism, combined with the progressive buildup of NM within the neuronal cytosol, may potentially contribute to the vulnerability of the dopaminergic system in TYR animals and in PD patients.…”
Section: Discussionsupporting
confidence: 64%
“… 57 In this context, it is important to recall that DAT is also expressed in astrocytes and macrophages, which contribute to DA clearance from the synaptic cleft. 48 , 49 The increased number of CD68- and GFAP-positive cells in AAV-TYR-injected animals could thus favor an increased DA uptake and metabolism in glial cells, which is consistent with increased 3MT levels observed in the ventral midbrain of AAV-TYR-injected animals at 2 months post-AAV injection ( Supplementary Table 6 ) and that could restrict the amount of DA available to be re-uptaken by neuronal DAT. All these changes in DA metabolism, combined with the progressive buildup of NM within the neuronal cytosol, may potentially contribute to the vulnerability of the dopaminergic system in TYR animals and in PD patients.…”
Section: Discussionsupporting
confidence: 64%
“…Some reports have shown that the disruption of iron homeostasis due to iron accumulation in dopamine neurons has been implicated in Parkinson’s disease [ 55 ]. GST catalyzes the modifying reaction of the reduced form of GSH to xenobiotic substrates in order to promote the solubility of xenobiotic substrates and prevent them from interacting with intracellular proteins and nucleic acids, to achieve the purpose of detoxification [ 56 ]. Therefore, the activation of Nrf2, in addition to increasing the amount of downstream GSH, should initiate multiple neuroprotective and antioxidative mechanisms, although these were not analyzed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have previously reported that striatal DAT levels are decreased by ∼70% in AAV-TYR-injected animals by 2 months post-AAV-TYR injections 5 , which concur with neuroimaging in vivo analyses in PD patients exhibiting reductions in DAT striatal density at early stages of the disease 51 . In this context, it is important to recall that DAT is also expressed in astrocytes and macrophages, which contribute to DA clearance from the synaptic cleft 46,47 . The increased number of CD68- and GFAP-positive cells in AAV-TYR-injected animals could thus favor an increased DA uptake and metabolism in glial cells, which is consistent with increased 3MT levels observed in the ventral midbrain of AAV-TYR-injected animals at 2 months post-AAV injection (Supplementary Table 4) and that could restrict the amount of DA available to be re-uptaken by neuronal DAT.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of the balance of cytosolic DA levels is complex and involves an interplay between different processes. From one hand, dopamine transporter (DAT)-mediated reuptake of extracellular DA [45][46][47] , leaking from synaptic vesicles, and TH-mediated DA synthesis increase cytosolic DA levels. On the other hand, VMAT2-mediated DA encapsulation into synaptic vesicles and MAO-mediated DA metabolism decrease cytosolic DA levels 48 .…”
Section: Discussionmentioning
confidence: 99%